PHARMACOVIGILANCE - Gunawan Widjaja; Yohanes Firmansyah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Pharmacovigilance is an activity that provides protection to patients and public health. Problems related to pharmacovigilance include: substandard drugs and counterfeit drugs, medication errors, reports of lack of drug efficacy, use of drugs with unapproved indications so that case reports of acute and chronic poisoning do not have a strong scientific basis, assessment of mortality due to drug use , drug abuse, and interactions with other drugs and foods. Pharmacovigilance reporting includes: spontaneous reporting, Individual Case Safety Report (ICSR), Periodic Safety Update Report (PSUR) / Periodic Benefit Risk Evaluation Report (PBRER). Furthermore, what is also important is the Summary of Risk Management Planning (RMP). The RMP provides key information related to research plans and other activities to gain more knowledge about drug safety and efficacy.